An Ounce of Prevention: Training Workers to Prevent a Crisis - Launa Mallett; Jr. Brnich; Charles Vaught (The National Institute for Occupational Safety and Health (NIOSH))
This paper introduces a technique for incorporating employee participation into the prevention component of a contingency plan. Companies sometimes focus so much energy on response that they forget to put resources into the basics of emergency prevention. The training program discussed here was designed to make employees part of the prevention system. Examples of training materials from the program are provided, a sample method for introducing risk assessment to employees is shown, and a strategy to address limited training time using short videos is explained. Methods for tailoring the training to any worksite and for specific risks are also included. The program is being designed and tested by the Pittsburgh Research Laboratory/NIOSH and employees of an underground coal mine. Examples are taken from the implementation of the program at the mine during the summer and fall of 1998. Results of the program evaluation and lessons learned during the implementation are discussed.